Christianity at the Frontiers. The Case of Rometta (Sicily) - Daniela Patti (Frontière·s)
During late antiquity, Christianity changed and expanded the boundaries and perspectives of the sacred. This is evident in the sacralization of borders through suburban sanctuaries, for example, and the use of the term limina in funerary epigraphy. The perception of physical spaces as sacred appears to have become fixed, which can be seen in the continual use of spaces that remain sacred in different periods and cultures. Research in the context of Rometta (Sicilia) may be connected to the conceptual category of the border, which is essential to the perception of space and the dynamics of identity. Rometta is a case in point: it was a pivotal location in the north-east of the island and the final frontier between the two dominant empires of the early medieval Mediterranean world, Byzantium and Islam. It is also a key reference point for Byzantine Sicilian archaeology and the site of the last resistance to Islamic domination. After mounting a desperate defence, it fell in 965 CE. Situated at the intersection of major roads and routes from the fertile plains of central Sicily to the Nebrodi mountains, Rometta represents the last stronghold of Byzantine culture in Sicily. Evidence of this can be seen in the archaeological remains of the 6th- to 9th-century Byzantine church of Santa Maria dei Cerei, as well as in the rock churches, one of which has several crosses carved into the rock and is probably related to an early Christian community.